Rapid cardiac care - Emma Menzies-Gow; Chrissie Spiers (Hoboken, New Jersey : Wiley Blackwell, 2018)
Rapid Cardiac Care is an indispensable resource for all frontline staff working with acutely ill patients. Offering easy access to the knowledge base needed to provide rapid, safe and effective cardiac care, it is ideal for newly qualified healthcare professionals including, nurses, paramedics, cardiac technicians, junior medics, and physiotherapists. Key features include: -Essential information to support the assessment of the cardiac patient including focused history taking and physical assessment, rhythm interpretation and 12-lead ECG assessment -Practical guidance on how to care for patients with cardiac emergencies, including acute coronary syndromes, arrhythmias, heart failure and cardiac arrest -A quick reference A-Z section that explores a wide range of conditions affecting the heart, each with a comprehensive overview of patient presentation and strategies to guide patient assessment and management -Diagrams and images are provided to facilitate learning
Keywords: Acute Disease therapy; Cardiovascular Diseases therapy; Cardiovascular Diseases diagnosis; Appareil cardiovasculaire Maladies Traitement